Investigating Risk Factors and Magnetic Resonance Imaging (MRI)-based Grading of Subchondral Incomplete Fracture (SIF) of Medial Femoral Condyle - Dong, Xiaoman; Zhang, Xiaoguang; Yu, Xiaokun; Meng, Xianghong; Zhang, Kaihui; Chen, Xiao; Guo, Lin; Wang, Zhi (Current Medical Imaging, 2024)
BackgroundSubchondral insufficiency fractures (SIF) of the knee joint are prevalent in osteoporosis patients over the age of 55. Early diagnosis of SIF fracture of the medial femoral condyle is crucial for delaying disease progression, early therapy, and potential disease reversal. Magnetic resonance imaging (MRI) is useful in detecting SIF, which is often undetectable on initial radiographs.This study aimed at developing a grading system for subchondral insufficiency fractures (SIF) based on MRI to predict outcomes and evaluate risk factors.MethodsIn this study, MRI was used to examine SIF risk variables in the medial condyle of the femur to help clinicians diagnose, treat, and delay the condition. A total of 386 patients with SIF from 2019 to 2021 were retrospectively analyzed and divided into 106 patients in the disease group and 280 patients in the control group according to whether they had SIF. The lesion site, meniscus, ligament, and other parameters were evaluated and compared. At the same time, a grading system was introduced to stratify and statistically analyze the size of the lesion area, the degree of bone marrow edema (BME), meniscus tears, and other parameters in the patients.ResultsMost SIF were low-grade (LG) fractures, and the predictors of LG and high-grade (HG) fractures included heel tear (P =0.031), degree of medial malleolus degeneration (P < 0.001), advanced age (P < 0.001), and lesion size (P < 0.001). The prognostic factors that showed significant differences between the two groups included age (P =0.027), gender (P =0.005), side (P =0.005), medial tibial plateau injury (P < 0.0001), femoral medullary bone marrow edema (P < 0.0001), medial tibial plateau bone marrow edema (P < 0.0001), meniscus body partial injury (P =0.016), heel tear (P =0.001), anterior cruciate ligament injury (P =0.002), and medial collateral ligament injury (P < 0.0001).ConclusionThis current study proposed an MRI-based grading system for inferior condylar fractures of the femur, in which HG inferior condylar fractures are associated with severe medial malleolus degeneration, advanced age, lesion size (correlation), and meniscus heel tears.
Keywords: LG inferior condylar fractures